Does leadership styles matter in Change Management Success? Employee performance as a proxy of effective change - Kee, Swee Lin; Lo, May Chiun; Ramayah, T.; Noornina, Dhalan (Journal of International Business and Entrepreneurship, Universiti Teknologi MARA (UiTM), 2007)
Past researchers have indicated that an effective change requires influencing employers positively and accomplishing group objectives. Managing change effectively in an organization is dependent on various factors and one of them is leadership style. The main purpose of this paper is to investigate the change effectiveness' dependence on leadership style. Data collected using a structured questionnaire showed that leadership style does influence effectiveness of change although out of 3 styles used only one; participative leadership style was a significant predictor of success. The paper outlines a clear link between various leadership styles and the success of change management. Furthermore, this paper identifies a major new source of strategic leadership value added in the companies' attention to creating processes and encouraging efforts for change management. Implications of the findings, potential limitations of the study, and directions for future research are suggested.